Varieties and politics of skill protection: a micro level analysis of unemployment protection systems in Europe - Feyertag, J (2013)
Varieties of Capitalism theory predicts that the skill specificity of workers determines their demand for social protection. In this thesis, I test this assumption using a measure of occupational mobility between pre- and post-unemployment, which I apply to European workers in different skill groups as defined by Fleckenstein et al., (2011). Using this measure as an indicator of the portability of workers' skills, I then evaluate whether the lower marketability of human capital investments is associated with greater demand for unemployment protection. The findings demonstrate that whilst this relationship is apparent in certain countries, notably Coordinated Market Economies such as Germany, the assumptions do not apply across institutional settings. Consequently, skill specificity cannot explain variation in attitudes towards unemployment protection policies between countries.